Vitamins Sales Before and During the COVID-19 Pandemic at Network Online Pharmacies in Indonesia - Happy Elda Murdiana; Mega Karina Putri; Aris Widayati; Dewi Rahmawati; Melia Eka Rosita (JURNAL INFO KESEHATAN, 2025)
The use of vitamins and micronutrients as an immunity enhancer during the COVID-19 pandemic is needed. The use of vitamins and micronutrients as immunity boosters during the COVID-19 pandemic is very much needed. The description of vitamin needs can be predicted from vitamin sales carried out by network online pharmacies in Indonesia. Vitamins C and E are antioxidants that indirectly have a role as an antiviral. Vitamin D can increase immunity, so its availability is important during the COVID-19 pandemic. This study compares vitamin sales before and during the COVID-19 pandemic at online pharmacies in Indonesia as a description of vitamin use in the community, and their availability by the pharmaceutical industry so that the government can take policies to accelerate this period. The study began by taking master data of all vitamin sales from January 2019 to December 2020 at one of the online pharmacies in Indonesia. Data on all sales each year were grouped based on vitamin content, namely single vitamins, containing two vitamins, and multivitamins (more than two vitamins) and then compared them. Data analysis used the independent t-test, and if the data was not normal and homogeneous, it was processed using the Mann-Whitney test by SPSS version 26 software. The results showed that there was a significant difference between sales of vitamin C (p<0.05), vitamin E (p<0.01), a combination of vitamins B and C (p<0.05), vitamins B and E (p<0.05), and multivitamins (p<0.001) in online pharmacy networks in Indonesia before and during the COVID-19 pandemic. Interestingly, sales of vitamin D did not increase significantly during the COVID-19 pandemic due to limited supplies from pharmaceutical companies even though vitamin D is very important for increasing immunity, thus giving rise to the policy of the Indonesian Ministry of Health to utilize sunlight as the main source of vitamin D.